2013
DOI: 10.4103/2277-9175.114177
|View full text |Cite
|
Sign up to set email alerts
|

Serum selenium levels in chronic lymphocytic leukemia

Abstract: Background:Selenium is a trace mineral which has the role of multiple biologic functions. In free-living animals and humans, selenium is mostly in the form of two selenium-containing amino acids as selenocysteine and selenomethionine. The present study aimed to obtain more data on the relationship between serum selenium in chronic lymphocytic leukemia (CLL).Materials and Methods:Serum selenium levels were measured in 51 patients with chronic lymphocytic leukemia (CLL) as patients group and in 40 non-hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The first hypothesis states that enhanced uptake of selenium by the neoplastic tissue might be responsible for depleting the trace element content in the blood and other tissues. Thereby, serum selenium concentrations are reduced (24). Secondly, the reduced Se concentration with disease progression might be due to dietary changes (10,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first hypothesis states that enhanced uptake of selenium by the neoplastic tissue might be responsible for depleting the trace element content in the blood and other tissues. Thereby, serum selenium concentrations are reduced (24). Secondly, the reduced Se concentration with disease progression might be due to dietary changes (10,24).…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, serum selenium concentrations are reduced (24). Secondly, the reduced Se concentration with disease progression might be due to dietary changes (10,24).…”
Section: Discussionmentioning
confidence: 99%
“…A causal inverse relationship between selenium and haematological malignancies exist (Azarm, Fazilati, Azarm & Azarm, 2013; Cai et al, 2016). An early clinical study reported a decrease in total leukocyte counts, immature leukocytes, and spleen size upon oral administration of selenium cystine (diseleno - dialanine) in patients with both CML and AML (Weisberger & Suhrland, 1956).…”
Section: Selenium-dependent Effects On Cancer Stem Cells In Leukemiamentioning
confidence: 99%